2015
DOI: 10.1152/ajpendo.00354.2014
|View full text |Cite
|
Sign up to set email alerts
|

A combination of exercise and capsinoid supplementation additively suppresses diet-induced obesity by increasing energy expenditure in mice

Abstract: Exercise effectively prevents the development of obesity and obesity-related diseases such as type 2 diabetes. Capsinoids (CSNs) are capsaicin analogs found in a nonpungent pepper that increase whole body energy expenditure. Although both exercise and CSNs have antiobesity functions, the effectiveness of exercise with CSN supplementation has not yet been investigated. Here, we examined whether the beneficial effects of exercise could be further enhanced by CSN supplementation in mice. Mice were randomly assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 60 publications
4
38
0
Order By: Relevance
“…Contrarily, serum cAMP levels were decreased in obese groups when compared to control group. These results were in agreement with Ohyama et al [43], who reported that the serum level of cAMP in obese was significantly lower than the non-obese rats. This may be due to the increase of FFAs and increased serum levels of mediators such as TNF-α, IL-1, IL-6, and NF-κB and reduced peroxisome proliferator-activated receptor gamma expression, resulting in overall decrease of serum cAMP [6].…”
Section: Resultssupporting
confidence: 93%
“…Contrarily, serum cAMP levels were decreased in obese groups when compared to control group. These results were in agreement with Ohyama et al [43], who reported that the serum level of cAMP in obese was significantly lower than the non-obese rats. This may be due to the increase of FFAs and increased serum levels of mediators such as TNF-α, IL-1, IL-6, and NF-κB and reduced peroxisome proliferator-activated receptor gamma expression, resulting in overall decrease of serum cAMP [6].…”
Section: Resultssupporting
confidence: 93%
“…In this study, we investigated the role of UCP1 in the anti-obesity effect of capsinoids by using WT and UCP1-KO mice. Consistent with previous reports (Ohyama et al, 2015), chronic treatment with capsinoids suppressed increases in body weight and body fat accumulation induced by HFD feeding of WT mice. Capsinoids showed no effect on the body weight gain or WAT weight increase of UCP1-KO mice fed HFD, indicating that the fat-reducing effect of capsinoids is mediated by UCP1.…”
Section: Discussionsupporting
confidence: 92%
“…For example, a single oral administration of capsinoids increases oxygen consumption in mice (Kawabata et al, 2009;Ohnuki et al, 2001) and humans (Inoue, Matsunaga, Satoh, & Takahashi, 2007;Josse et al, 2010). Chronic treatment with capsinoids reduces body fat in mice (Ohnuki et al, 2001) and humans (Faraut et al, 2009;Snitker et al, 2009) and prevents high-fat diet-induced obesity (Ohyama et al, 2015). In addition, several studies have suggested the involvement of BAT or UCP1 in the effect of capsinoids.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that exercise increases the levels of cAMP [33] and curcumin has also been reported to have this effect as measured by inhibition of endothelial cell phosphodiesterase (PDE) [34]. Curcumin indeed increased cAMP levels ( …”
Section: Curcumin Treatment Increases Camp Levelmentioning
confidence: 98%